Efficacy Evaluation of Dabur Dia Control Juice, an Ayurvedic Formulation as an Adjuvant in NIDDM - Baidyanath Mishra; Srinivasa Yathapu; Simadri Nayak; Sushanta Sahu; Garima Gupta; Apratim Rajesh (European Journal of Preventive Medicine, 2026)
Global burden of Type 2 Diabetes Mellitus (T2DM) has reached alarming proportions, with prevalence surging from 200 million to over 830 million over three decades. India bears a disproportionate share of this crisis, with approximately 77 million individuals living with T2DM and an additional 25 million in the prediabetic range (HbA1c: 5.7–6.4%), collectively imposing significant threats to workforce productivity and national healthcare expenditure. While anti-hyperglycemic (AHG) agents combined with lifestyle modifications remain the cornerstone of T2DM management, long-term dependence on escalating pharmacological doses and the risk of chronic complications have intensified interest in adjunctive therapeutic strategies. In this context, the present study evaluated the adjunctive efficacy and safety of a proprietary ayurvedic formulation (sugar-free juice), DRDC/2025/010, in individuals with T2DM already on standard AHG therapy. This ethically approved, CTRI-registered clinical study enrolled 30 T2DM participants screened against predefined inclusion and exclusion criteria. Participants received 30 mL of DRDC/2025/010 diluted in 250 mL of drinking water, consumed twice daily for 90 days, alongside their existing AHG regimen, dietary guidance, and exercise routine. Efficacy endpoints included fasting blood sugar (FBS), random blood sugar (RBS), glycated hemoglobin (HbA1c), body mass index (BMI), and quality of life (QoL). Safety was monitored through biochemical parameters, vital signs, and adverse event (AE) surveillance throughout the study period. DRDC/2025/010 demonstrated statistically significant reductions in FBS at Day 60 ( p < 0.05 ) and Day 90 ( p < 0.0001 ), and in RBS at Day 60 ( p < 0.05 ) and Day 90 ( p < 0.0001 ), relative to baseline. A significant (P